ΑII‐spectrin controls calcium‐regulated exocytosis in neuroendocrine chromaffin cells through neuronal Wiskott–Aldrich Syndrome protein interaction. Issue 4 (20th December 2019) - Houy, Sébastien; Nicolas, Gaël; Momboisse, Fanny; Malacombe, Magali; Bader, Marie‐France; Vitale, Nicolas; Lecomte, Marie‐Christine; Ory, Stéphane; Gasman, Stéphane
Abstract: Besides a fundamental structural role at the plasma membrane, spectrin‐ and actin‐based skeletons have been proposed to participate in various processes including vesicular trafficking. Neuroendocrine cells release hormones and neuropeptides through calcium‐regulated exocytosis, a process that is coordinated by a fine remodeling of the actin cytoskeleton. We describe here that calcium‐regulated exocytosis is impaired in chromaffin and PC12 cells with reduced αII‐spectrin expression levels. Using yeast two‐hybrid screening, we show that neuronal Wiskott–Aldrich Syndrome protein (N‐WASP) is a partner of the αII‐spectrin SH3 domain and demonstrate that secretagogue‐evoked N‐WASP recruitment at cell periphery is blocked in the absence of αII‐spectrin. Additionally, experiments performed with ectopically expressed αII‐spectrin mutant unable to bind N‐WASP indicated that the interaction between SH3 domain and N‐WASP is pivotal for neuroendocrine secretion. Our results extend the list of spectrin interactors and strengthen the idea that αII‐spectrin is an important scaffold protein that gathers crucial actin‐related players of the exocytic machinery.